2010
DOI: 10.1002/pssb.201046378
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of nanowires

Abstract: The elastic properties of metallic and semiconducting nanowires were analyzed by different techniques employing static and dynamic loads. The reliability of the methods is verified by analyzing well defined microstructures and a good agreement for the values of the Young's modulus determined by the different methods was achieved. For the investigated materials systems (Au, W, Si, InN), basically no differences in the Young's moduli were observed between microstructures, bulk material, and nanowires with radii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 89 publications
3
17
1
Order By: Relevance
“…These results contrast with the different conclusions drawn on the impact of size reduction on Young's modulus of metals or semiconductors from mechanical or electromechanical studies performed on nanowires of relatively large size (larger than 20 nm) [3,[182][183][184][185]. Depending on the experimental conditions, these nanomanipulation-based methods suggested either stiffening, or softening or no modification of the material elasticity below few tens of nanometers.…”
Section: Small Spherical Clusterscontrasting
confidence: 81%
See 1 more Smart Citation
“…These results contrast with the different conclusions drawn on the impact of size reduction on Young's modulus of metals or semiconductors from mechanical or electromechanical studies performed on nanowires of relatively large size (larger than 20 nm) [3,[182][183][184][185]. Depending on the experimental conditions, these nanomanipulation-based methods suggested either stiffening, or softening or no modification of the material elasticity below few tens of nanometers.…”
Section: Small Spherical Clusterscontrasting
confidence: 81%
“…Depending on the experimental conditions, these nanomanipulation-based methods suggested either stiffening, or softening or no modification of the material elasticity below few tens of nanometers. The dispersion of the conclusions suggests a large influence of the measurement method, probably due to mechanical interaction with the nano-objects, and possible artifacts due to crystallinity defects or surface contamination or oxidation [185,186]. The former problem is avoided in non-contact optical techniques, while the latter stresses the importance of controlling the particle surface [71].…”
Section: Small Spherical Clustersmentioning
confidence: 99%
“…In future, we can expect some non-destructive testing (NDT) techniques for mechanical testing of these nanostructures. An interested reader may go through a comprehensive review article by Rohlig et al 130 where different techniques for evaluating elastic properties of NWs have been covered.…”
Section: E Mechanical Propertiesmentioning
confidence: 99%
“…More recently, both experimental and theoretical investigations specifically indicated that the oxide-coated NWs exhibit different mechanical properties than their pure (unoxidized) counterparts. For example, oxide-coated tungsten NWs exhibit increased Young's modulus, 22 whereas it decreases in oxide-covered silicon 23 and copper NWs. 24 Sen et al have also studied oxide shell layer dependent deformation mechanisms of metallic aluminum NWs by using the ReaxFF model.…”
Section: Introductionmentioning
confidence: 99%
“…24 Sen et al have also studied oxide shell layer dependent deformation mechanisms of metallic aluminum NWs by using the ReaxFF model. 21,22 The authors observed that the oxide amorphous shell layer on the Al NW free surface enhances dislocation processes, as well as the Al core's dislocation nucleation stress. Most importantly, the presence of native amorphous oxide shell layers on Al NWs was shown to play a significant role in the change in the elastic mechanical response from brittle to ductile transition behavior.…”
Section: Introductionmentioning
confidence: 99%